2008
DOI: 10.1117/12.769440
|View full text |Cite
|
Sign up to set email alerts
|

A web-accessible content-based cervicographic image retrieval system

Abstract: Content-based image retrieval (CBIR) is the process of retrieving images by directly using image visual characteristics. In this paper, we present a prototype system implemented for CBIR for a uterine cervix image (cervigram) database. This cervigram database is a part of data collected in a multi-year longitudinal effort by the National Cancer Institute (NCI), and archived by the National Library of Medicine (NLM), for the study of the origins of, and factors related to, cervical precancer/cancer. Users may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…CervigramFinder incorporates fundamental CBIR functions, such as feature extraction, feature normalization, feature combination, feature dimension reduction, and similarity measures [9]. We did an extensive study on evaluating and identifying key techniques among those found in the technical literature by comparing their performance for the retrieval of cervigrams.…”
Section: Cbir Functionsmentioning
confidence: 99%
“…CervigramFinder incorporates fundamental CBIR functions, such as feature extraction, feature normalization, feature combination, feature dimension reduction, and similarity measures [9]. We did an extensive study on evaluating and identifying key techniques among those found in the technical literature by comparing their performance for the retrieval of cervigrams.…”
Section: Cbir Functionsmentioning
confidence: 99%
“…CervigramFinder is a Web-accessible contentbased image retrieval (CBIR) prototype system for searching cervigrams by their visual attributes [3]. It operates on an expert-annotated subset of the NCI cervigram data for which the lesion regions-of-interest (ROI) have been manually pre-marked and labeled by NCI medical experts [4].…”
Section: Figure 1 Sample Cervigram Imagementioning
confidence: 99%
“…• Normalized center of the region (3) where, N is the total number of pixels in the region and , are the angle and range, respectively, associated with point i.…”
Section: Figure 2 Cervigramfinder Guimentioning
confidence: 99%
“…For this purpose a content based image retrieval (CBIR) system could be used [11,14,19], both to benefit the management of increasingly large image collections, and to support clinical care, biomedical research, and education. However, although the number of experimental algorithms comprehending specific problems and databases is growing, few systems exist with relative success [3,7,29]. So, biomedical applications are one of the priority areas where CBIR can meet more success outside the experimental sphere, due to population aging in developed countries.…”
Section: Introductionmentioning
confidence: 99%